Cheria Video Conference to Improve Students’ English Ability and Character at SMA 3 Padang - Refnita Refnita (English Language Teaching and Research, 2018)
The purpose of learning English for Senior High School students is to make students able to use spoken and written language in interpersonal, transactional, functional and essay text. This target quite difficult to be reached since the time allocation for learning English is only 2 hours (90 minutes) a week. To give chance for students who are interested in learning English, the school provide an English club, namely the English community. This club is a kind of extracurricular activity. The meeting which was held every week after the school hours initially attended by many students. However, the number of students decreased week by week. After interviewing them, it was found some reasons that make them lazy to attend the meeting. They were tiredness, having other kinds of extracurricular activity, and boring activities. They need something to challenge them to speak with people from other countries. To overcome this problem, the teacher used Cheria Video Conference. Cheria is the acronym of Chatting through Social Media and Video Conference. Cheria is done as the replacement of the meeting. Since the students are close with social media, so the teacher used social media Line and Whatsapp to discuss the topic for incoming Videoconference. Through Generation Global, students could share ideas with other students from other countries about many topics such as community, faith, charity, celebration, and many others. Moreover, this activity also could make them practice their English and well as building their characters such as nationalism, religious, collaboration, integrity, and independent. Key words: Cheria, Video Conference, characters